Investigation of Single-Phase Flow Characteristics in an Inline Pin-Fins Complex Geometry. Issue 3 (May 2021) - Shakir, R.
Abstract: In this guess investigation of concerns R113 heat transfer of pressure drop flow in single-phase flow in inline on the square shape of micro-channel of pin-fins own a (5×5 mm2) cross-area segment section via of (5 mm) heightly. Therefore, the inline square micro-channel of pin-fins complex geometry additionally owning (25) numbers of the pin-fins, total pin-fins channel dimension (50 mm × 50 mm). Subsequently. The liquid has (25°C) inlet temperature for the same inlet temperature six mass flow rates were applied, ranging from (0.0025 - 0.01 kg/sec), and heat apply ranged from (40-200 Watts). Guess single-phase heat transfer coefficients, guess liquid temperatures and guess wall temperatures were reported in this investigation.